APPLICATION OF COUNTEXTUAL TEACHING AND LEARNING APPROACH TO IMPROVE LEARNING OUTCOMES OF CUBE AND BEAM PROPERTIES IN CLASS IV STUDENTS SDN 8 RIOPAKAVA - Akina Akib; Komang Armada (Universitas Tadulako, 2019)
This research aims to improve mathematics learning outcomes using countextual teaching and learning approach of the students in grade IV of SDN 8 Riopakava this was a classroom action research conducted in 2 cycles and each cycle consisted of four stages, namely: (a) planning, (b) action, (c) observation, and (d) reflection. The problem want to be exzamined is the low learning outcomes. The effort to solve it is by applying Countextual Teaching And Learningapproach. the subjects of the research were 23 students of the school consisted of 7 males and 16 fameles. The research results reveal that in cycle I classical learning achievementwas 56,52% while in cycle II was 91,08%. Based on the percentage of learning achievement in cycle I and II, then, the increase was 34,71% from cycle I to cycle II. Therefore, it can be concluded that the use of Countextual Teaching And Learning approach can improve learning outcomes of the students in grade IV of SDN 8 Riopakava.